A Mixed Blessing? Explaining the Double-Edged Effects of Leader Leniency on Employee Task Performance - Liu, Xin (Journal of business ethics, 2024)
Leaders are often faced with the dilemma as to how to respond to employee misconduct. However, scholarly accounts of leader actions in such situations have primarily focused on punishment as a mechanism for dealing with employee misconduct. Leader leniency, an alternative response that is often adopted in practice, has been largely overlooked. Consequently, in order to provide a more complete account of leader responses to employee misconduct and to clarify whether leader leniency is effective, we investigate the potential double-edged influences of leader leniency on employee task performance. Specifically, we propose that leader leniency inhibits employee task performance through the mediating role of psychological entitlement, while it also has beneficial effects on employee task performance through the mediating role of servant leadership perception. Moreover, trait moral disengagement serves as a vital boundary condition, which amplifies the negative influence of leader leniency through psychological entitlement and simultaneously mitigates its positive effect through servant leadership perception. Results from an experience sampling study and a scenario-based experiment supported our hypotheses. Our work highlights the mixed blessing of leader leniency and clarifies when and how leader leniency rehabilitates wrongdoers or instead propels them to further down the path of misconduct.